Effect of exercise training on enos expression, NO production and oxygen metabolism in human placenta (2013)
Abstract Objective To determine the effects of combined aerobic and resistance exercise training during the second half of pregnancy on endothelial NOS expression (eNOS), nitric oxide (NO) production and oxygen metabolism in human placenta. Methods The study included 20 nulliparous in gestational week 16–20, attending prenatal care at three tertiary hospitals in Colombia who were randomly assigned into one of two groups: The exercise group (n?=?10) took part in an exercise session three times a week for 12 weeks which consisted of: aerobic exercise at an intensity of 55–75% of their maximum heart rate for 60 min and 25 mins. Resistance exercise included 5 exercise groups circuit training (50 repetitions of each) using barbells (1–3 kg/exercise) and low-to-medium resistance bands. The control group (n?=?10) undertook their usual physical activity. Mitochondrial and cytosol fractions were isolated from human placental tissue by differential centrifugation. A spectrophotometric assay was used to measure NO production in cytosolic samples from placental tissue and Western Blot technique to determine eNOS expression. Mitochondrial superoxide levels and hydrogen peroxide were measured to determine oxygen metabolism. Results Combined aerobic and resistance exercise training during pregnancy leads to a 2-fold increase in eNOS expression and 4-fold increase in NO production in placental cytosol (p?=?0.05). Mitochondrial superoxide levels and hydrogen peroxide production rate were decreased by 8% and 37% respectively in the placental mitochondria of exercising women (p?=?0.05). Conclusion Regular exercise training during the second half of pregnancy increases eNOS expression and NO production and decreases reactive oxygen species generation in human placenta. Collectively, these data demonstrate that chronic exercise increases eNOS/NO production, presumably by increasing endothelial shear stress. This adaptation may contribute to the beneficial effects of exercise on the vascular and antioxidant system and in turn reduce the risk of preeclampsia, diabetes or hypertension during pregnancy.